Cholesterol lowering in intermediate-risk persons without cardiovascular disease - Yusuf, Salim; Bosch, Jackie; Dagenais, Gilles; Jun, Zhu; Xavier, Denis; Lisheng, Liu; Md Aris, Mohd Aznan; Mohd Shah, Azarisman Shah; ., et. al (Massachusetts Medical Society, 2016)
Previous trials have shown that the use of statins to lower cholesterol reduces the risk of cardiovascular events among persons without cardiovascular disease. Those trials have involved persons with elevated lipid levels or inflammatory markers and involved mainly white persons. It is unclear whether the benefits of statins can be extended to an intermediate-risk, ethnically diverse population without cardiovascular disease.